2016
DOI: 10.1007/s11307-016-1027-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TSPO PET Ligands [18F]VUIIS1009A and [18F]VUIIS1009B: Tracers for Cancer Imaging

Abstract: Purpose Positron emission tomography (PET) ligands targeting translocator protein (TSPO) are potential imaging diagnostics of cancer. In this study, we report two novel, high-affinity TSPO PET ligands that are 5,7 regioisomers, [18F]VUIIS1009A ([18F]3A) and [18F]VUIIS1009B ([18F]3B), and their initial in vitro and in vivo evaluation in healthy mice and glioma-bearing rats. Procedures VUIIS1009A/B was synthesized and confirmed by X-ray crystallography. Interactions between TSPO binding pocket and novel ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…Of these radiotracers, 18 F-VUIIS1009A and 18 F-VUIIS1009B demonstrate over 500-fold higher binding a nities when compared to the parent radiotracer 18 F-DPA-714. Imaging with these two radiotracers in C6 glioma model also demonstrates the superiority of 18 F-VUIIS1009B to 18 F-VUIIS1009A and 18 F-DPA-714, including higher BP ND , higher SNR and higher total distribution volume (V T ) [22].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Of these radiotracers, 18 F-VUIIS1009A and 18 F-VUIIS1009B demonstrate over 500-fold higher binding a nities when compared to the parent radiotracer 18 F-DPA-714. Imaging with these two radiotracers in C6 glioma model also demonstrates the superiority of 18 F-VUIIS1009B to 18 F-VUIIS1009A and 18 F-DPA-714, including higher BP ND , higher SNR and higher total distribution volume (V T ) [22].…”
Section: Introductionmentioning
confidence: 89%
“…Based on the scaffold of 18 F-DPA-714, many novel radiotracers have been developed and introduced in both clinical and preclinical TSPO PET imaging, including 18 F-DPA-C5yne [19], 18 F-VUIIS1008 [20,21], 18 F-VUIIS1009A/B [22], 18 F-FDPA [23], 18 F-VUIIS1018A [24,25]. Of these radiotracers, 18 F-VUIIS1009A and 18 F-VUIIS1009B demonstrate over 500-fold higher binding a nities when compared to the parent radiotracer 18 F-DPA-714.…”
Section: Introductionmentioning
confidence: 99%
“…13 Subsequent in vivo studies of [ 18 F]- 2b demonstrated this agent to possess several properties for molecular imaging of TSPO-expressing cancers. 13,21 …”
mentioning
confidence: 99%
“…Subsequent preclinical studies illuminated [ 18 F]- 14 as a promising, novel TSPO PET ligand for imaging glioma. Compared to previous TSPO PET ligands in oncology, the first generation ligand [ 11 C]PK11195 39 and the second generation ligands [ 18 F]PBR06, 19 [ 18 F]DPA-714, 12 and [ 18 F]VUIIS1008, 13,21 [ 18 F]- 14 has demonstrated improved binding affinity and in vivo imaging characteristics. These advantages, in addition to the in vivo stability and high signal-to-noise achieved between tumor and surrounding normal brain, suggest the potential of this PET ligand for detection of TSPO-expressing tumors in the brain and neuroinflammation.…”
mentioning
confidence: 99%
See 1 more Smart Citation